Prevalensi Stunting, Underweight, Wasting pada Balita di UPT Puskesmas Tetaf Tahun 2025 - Firfis P. Ninu; Intje Picauly (PPNI UNIMMAN, 2026)
Malnutrition among children under five remains a major public health concern, particularly in areas with limited access to nutritious food and health services. This study aimed to determine the prevalence of stunting, underweight, and wasting among children under five in Kuatnana District, South Central Timor Regency in 2025. This research used a descriptive cross-sectional design with secondary data obtained from nutrition program reports at Tetaf Public Health Center. The sample included all children aged 0–59 months, totaling 1,179 children. Data were analyzed using univariate analysis to calculate frequency distribution and percentages based on WHO anthropometric indicators (z-score). The results showed that the prevalence of stunting was 44.78%, underweight 40.46%, and wasting 14.76%. Most children had normal nutritional status based on weight-for-height index (88.38%), although a considerable proportion still experienced undernutrition. In conclusion, malnutrition among children under five in Kuatnana District remains high, particularly stunting and underweight. Integrated interventions are needed, including improving caregiving practices, increasing access to nutritious food, and strengthening health services to reduce malnutrition sustainably.